Practice-oriented approach to teaching Python programming to university students - Kapbar, Gulsim; Karymsakova, Anara (Scientific Herald of Uzhhorod University Series Physics, 2024)
Relevance. The study on this topic is relevant due to the growing need for practical skills to enhance graduate competitiveness, advances in technology, and demands for real-world problem-solving. Purpose. The purpose of this study was to evaluate the effectiveness of a practice-oriented approach to teaching Python programming in higher education institutions to optimise curricula and make students better prepared for the demands of modern industry. Methodology. The methods used include an analytical method, experimental method, comparative method, synthesis method, modelling method, classification method, and statistical method. Results. The study found a considerable increase in academic performance, an increase in interest in the subject and the development of practical skills, which emphasises the significance of the practice-oriented approach in university education. Conclusions. The study concluded that the practice-oriented approach significantly improved the quality of learning, student satisfaction, and practical skills. This educational approach not only enhanced learning efficiency but also better-prepared students for successful careers in programming. The practical value lies in providing students with real software development skills, boosting their competitiveness in the job market, and ensuring successful adaptation to the information technology industry. Keywords: curricula; innovations in education; modern technologies; assessment of educational results